Predisposing factors for recanalization of cerebral aneurysms after endovascular embolization: a multivariate study. (4th April 2017) - Zhang, Qianqian; Jing, Linkai; Liu, Jian; Wang, Kun; Zhang, Ying; Paliwal, Nikhil; Meng, Hui; Wang, Yang; Wang, Shengzhang; Yang, Xinjian
Abstract : Background: The recanalization of cerebral aneurysms after endovascular embolization (coiling or stent-assisted coiling) has been a matter of concern. Objective: To systematically evaluate the predisposing factors for cerebral aneurysm recanalization using multidimensional analysis in a large patient cohort. Methods: In 238 patients with 283 aneurysms, patient baseline characteristics, aneurysm morphological characteristics, treatment-related factors, and changes in flow hemodynamics after endovascular treatment (coiling or stent-assisted coiling) were compared between the recanalization and non-recanalization groups. Multivariate logistic regression analysis was performed to determine independent risk factors correlated with recanalization. Results: 16 aneurysms treated by coiling recanalized, with a recurrence rate of 18.6%, and 24 recanalized in the lesions treated by stent-assisted coiling, with a recanalization rate of 12.2%. Large aneurysms (>10 mm, p=0.002) and a follow-up interval >1 year (p=0.027) were shown to be statistically significant between the recanalization and non-recanalization groups. For flow hemodynamic changes, three parameters (velocity on the neck plane, wall shear stress on the neck wall, and wall shear stress on the whole aneurysm) showed a relatively lower amplitude of decrease after endovascular treatment in the recanalization group. Interestingly, the velocity on the neck plane and wall shear stress on the neck wall may be elevated after treatment. Specifically, the reduction ratio (RR) of velocity on the neck plane showed significant difference between the groups in the multivariate analysis (p=0.013), and was considered an independent risk factor for recanalization. Conclusions: The aneurysm size, follow-up interval, and flow hemodynamic changes, especially the RR of velocity on the neck plane, have important roles in aneurysm recanalization.